Maximizing Profitability Through Material Management: Achieving Profitability through Effective Material Management (Journal of Advances and Scholarly Researches in Allied Education, 2011)
One of the problems facing Manufacturing Company is the growing trend towards the higher cost ofmaterials and services and constant shut down of factory, which erode business profit. The paperfocuses on how business firm can attain profitability through effective management of materials. The objective of this paper is to identity problems of material management, which if corrected can result inprofitability. The paper also examines and outlines the roles and benefits of materials management.Secondary data and primary data were utilized in this study. The finding shows that there is need torecognize the materialsmanagement function and it has been suggested that for a firm to achieve profitability,the goal of materials management outlined in this paper should be properly carried out.